CHILDHOOD: WHAT WE UNDERSTAND AND DO NOT UNDERSTAND - Černova, Emīlija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
"What is childhood?" - an educated person today would answer that childhood is the stage of a child’s growing up to achieve social maturity and becoming a  responsible member of society. A person when he/she is at the life period between infancy and youth is not recognized as an adult (Hanson, 2009). Blonsky noted that 33% of a person’s life-span belongs to his/her childhood (Blonskis, 1920). The stages of human childhood are a product of history. These are subject to changes just like thousands of years ago. Historically, childhood is not mainly related to the state of biological maturity, but to the specific social status of a person which manifests itself in the roles of duties and rights of a particular stage of life, with appropriate kinds and forms of activity, as well as responsibility.  The 21st century’s socialization theory draws the child's image as an active and competent person, who deserves being allowed to determine his own choices and actions in the process of socialization (Corsaro, 1997, Jamess, Proud, 2013). Researchers (for instance, Woodrow, 1999) highlight that a child is considered to be equivalent to an adult, but in the process of upbringing all its participants have the opportunity to cooperate by sharing power among those being involved and delegating responsibility. Therefore, it is important to get to know what is an image of a modern child in the perception and notions of adults (parents, teachers, other members of society) who are no longer child-carers or currently are not related to this work. What are we ‘adults’ like in the eyes of a child? Dominant research methods: adult written surveys, interviews with children.